Environment-friendly and efficient degreasing process for photovoltaic aluminum profile frame

CN122727809APending Publication Date: 2026-09-11JIANGSU SUA ALUMINUM PRECISION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610871360.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

[0002]光伏组件边框通常采用铝型材制成,具有质量轻、强度高、耐候性好和便于装配等优点,在铝型材边框的挤压、切割、冲孔、组角和转运过程中,型材表面及槽腔内易残留挤压油、切削液、防锈油、润滑脂、金属屑和粉尘等污染物,若上述油污未被充分去除,会影响后续氧化、喷涂、粘接、密封及装配质量,导致涂层附着力下降、胶接不牢、表面发花、水印或局部腐蚀等问题

Benefits of technology

[0033] 1. This invention utilizes a weak alkaline buffer system formed by sodium carbonate and sodium bicarbonate to promote the neutralization of acidic oil stains and the saponification of some ester-based oil stains, while avoiding significant corrosion of the aluminum substrate and its oxide film by strong alkali. Alkyl glycosides and low-foaming surfactants enhance wetting and emulsifying capabilities, while tetrasodium glutamate diacetate and sodium gluconate inhibit metal ion-induced soap scum and deposition. CO2 reversible interfacial migration microgel powder inserts into the oil stain interface through hydrophobic segments, and reversibly bridging polyurethane salts achieve oil stain capture, dispersion, and complexation through carboxylates, hydrophobic segments, and amine groups, thereby reducing the interfacial bonding force between oil stains and the aluminum surface, allowing the organic oil film to be fully peeled off. This improves the oil removal rate, reduces the water contact angle, and simultaneously provides phosphorus-free environmental protection and aluminum surface protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses an environment-friendly and efficient degreasing process for a photovoltaic aluminum profile frame, and belongs to the technical field of aluminum degreasing, and specifically comprises the following steps: adding sodium carbonate and sodium bicarbonate into deionized water, and adding alkyl polyglycoside, low-foam surfactant, tetrasodium glutamate diacetate, sodium gluconate, reversible bridged polyamino acid salt, CO2 reversible interface migration microgel powder, tannic acid and defoaming agent into a reaction system. The application realizes efficient and environment-friendly degreasing of the photovoltaic aluminum profile frame through cooperation of weak alkali system, CO2 response functional components and reversible bridged polyamino acid salt, and maintains the oil removal rate and water contact angle after continuous operation for 100 hours, so that the stable degreasing effect is maintained, and the phosphorus-free environment-friendly performance is also possessed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum degreasing technology, specifically to an environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames. Background Technology

[0002] Photovoltaic module frames are typically made of aluminum profiles, which have advantages such as light weight, high strength, good weather resistance, and ease of assembly. During the extrusion, cutting, punching, corner assembly, and transportation of aluminum profile frames, contaminants such as extrusion oil, cutting fluid, rust-preventive oil, lubricating grease, metal shavings, and dust can easily remain on the surface and inside the grooves. If these oil stains are not fully removed, they will affect the quality of subsequent oxidation, spraying, bonding, sealing, and assembly, leading to problems such as reduced coating adhesion, weak bonding, surface discoloration, watermarks, or localized corrosion.

[0003] Currently, the frames of photovoltaic aluminum profiles are not simple planar structures. They often have complex structures such as C-shaped grooves, corner code grooves, mounting holes, and drainage holes. Conventional soaking or continuous spraying methods have a good cleaning effect on the outer surface, but they are not sufficient to remove oil stains from the bottom of the groove, corner positions, and pore areas. This can easily lead to local water contact angles being too high and grease residues exceeding the standard, affecting the consistency of subsequent treatments.

[0004] Traditional degreasing solutions contain phosphates, silicates, strong alkalis, complexing agents, and surfactants. Although they have a certain degreasing ability, they still have problems such as high environmental load, difficulty in wastewater treatment, and insufficient long-term operational stability. Furthermore, the discharge of phosphorus-containing degreasing agents can easily cause eutrophication of water bodies, and the strong alkaline system may corrode aluminum substrates and their oxide films, resulting in rough, dull, or alkaline-stained surfaces of the profiles.

[0005] In addition, during continuous production, the degreasing liquid will continuously absorb oil, metal ions and particulate impurities. As the degreasing liquid gradually accumulates, it can easily cause a decrease in cleaning ability, an increase in foam, oil back-sticking and an increase in rinsing load, resulting in a short service life of the degreasing liquid, a large amount of reagent consumption and a high amount of waste liquid, which is not conducive to continuous, low-cost and environmentally friendly production.

[0006] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0007] The purpose of this invention is to provide an environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames, which solves the technical problem that the degreasing and cleaning capabilities and recyclability of photovoltaic aluminum profile frames in the prior art need to be further improved.

[0008] The objective of this invention can be achieved through the following technical solution: an environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames, comprising the following steps:

[0009] S1. Add sodium carbonate and sodium bicarbonate to deionized water, adjust the pH of the system to 9-10, add alkyl glycoside, low foaming surfactant, tetrasodium glutamate diacetate, sodium gluconate, reversible bridging polyurethane salt, CO2 reversible interfacial migration microgel powder, tannic acid, and defoamer to the reaction system, heat the reaction system to 50-60℃, and stir until the system is dissolved to obtain a phosphorus-free weak alkaline degreasing solution.

[0010] A weak alkaline buffer system is formed by combining sodium carbonate and sodium bicarbonate, which stabilizes the pH of the degreasing solution within the range of 9.2-9.8, neutralizing acidic oil stains and producing a mild saponification effect on some ester-based oil stains, while avoiding significant corrosion of the aluminum substrate and its oxide film by strong alkali. Alkyl glycosides and low-foaming surfactants reduce the surface tension of the system, improve the wetting ability of the degreasing solution on the outer surface, grooves and pores of aluminum profiles, and promote oil emulsification and peeling. Tetrasodium diacetate and sodium gluconate can complex calcium, magnesium, iron and aluminum ions, reducing metal soap, deposits and inorganic salt residues, and avoiding secondary pollution or increased contact angle caused by these deposits. Tannic acid can form a certain coordination adsorption with metal surfaces or metal ions, which helps to reduce the activation and localized corrosion of aluminum surfaces in a weak alkaline environment. Defoamers ensure that foam is controlled during spraying and circulation, avoiding foam carrying oil stains and affecting the spray impact force, so that the degreasing solution has both strong degreasing ability and good aluminum material adaptability and long-term stability.

[0011] S2. Add phosphorus-free weak alkaline degreasing solution to the degreasing tank, control the temperature of the degreasing solution to 35-42℃ and the pH to 9.2-9.8, place the photovoltaic aluminum profile frame to be treated on the conveyor hanger, and let the photovoltaic aluminum profile frame pass through the pre-wetting zone for pre-wetting, the main degreasing zone for degreasing, the tank cavity drainage zone for drainage, and the rinsing and drying zone for washing and drying to obtain the degreased photovoltaic aluminum profile frame.

[0012] S3. During the degreasing process, the degreasing liquid collected in the main degreasing zone and the draining zone of the tank cavity is transported to the regeneration tank for regeneration to obtain degreasing regeneration liquid, which is then recycled for reuse.

[0013] Furthermore, in step S1, the weight ratio of sodium carbonate to sodium bicarbonate is 3:2, and the dosage ratio of deionized water, alkyl glycoside, low-foaming surfactant, tetrasodium diacetate of glutamate, sodium gluconate, reversible bridging polyurethane salt, CO2 reversible interfacial migration microgel powder, tannic acid, and defoamer is 1L:0.26-0.35g:0.11-0.15g:0.9-1.2g:0.4-0.6g:0.22-0.26g:0.4-0.5g:0.03-0.05g:0.03-0.05g.

[0014] Furthermore, the preparation method of reversible bridged polyurethane salt is as follows: polysuccinimide and N-methylpyrrolidone are mixed and stirred, the reaction system is heated to 55-65℃ and stirred until the system is dissolved, laurylamine and N,N-dimethyl-1,3-propanediamine are added to the reaction system, the reaction is kept at the temperature for 6-8 hours, sodium hydroxide aqueous solution is added to the reaction system to adjust the pH of the system to 9-10, the reaction is kept at the temperature for 3-4 hours, and the reversible bridged polyurethane salt is obtained after post-treatment.

[0015] The synthesis mechanism of reversible bridged polyurethane salts is as follows:

[0016] The polysuccinimide molecular chain contains a cyclic imide structure. During the reaction, after the polysuccinimide dissolves in N-methylpyrrolidone, the amino groups in laurylamine and N,N-dimethyl-1,3-propanediamine can nucleophilically attack the imide ring, causing the imide ring to open and form an amide structure. Laurylamine introduces long-chain alkyl hydrophobic groups, enhancing the polymer's adsorption and anchoring ability for oil stains. N,N-dimethyl-1,3-propanediamine introduces a tertiary amine structure, giving the polymer pH-responsive and CO2-responsive characteristics. Adding sodium hydroxide to adjust the system to pH 9-10 promotes further alkaline hydrolysis of the incompletely amino-degraded imide ring, forming a polyurethane salt structure.

[0017] The resulting polymer simultaneously contains carboxylates, amide bonds, hydrophobic alkyl chains, and tertiary amine groups. The carboxylates can complex metal ions and provide dispersion stability, the hydrophobic segments can adsorb oil, and the tertiary amine groups readily undergo protonation when the pH is lowered by CO2, thereby altering the polymer's charge state and hydrophilic-hydrophobic balance. During the degreasing stage, this polymer can disperse oil droplets, complex metal ions, and inhibit soap scum deposition and oil back-adhesion. During the regeneration stage, CO2-induced protonation and charge changes facilitate bridging, coalescence, and flotation separation between oil droplets. Therefore, the reversibly bridging polyurethane salt not only improves initial degreasing capacity but also reduces performance degradation caused by emulsified oil accumulation during continuous operation, maintaining a high oil removal rate after 100 hours and keeping the water contact angle within a low range.

[0018] Furthermore, the ratio of polysuccinimide, N-methylpyrrolidone, laurylamine, and N,N-dimethyl-1,3-propanediamine is 10g:60-100mL:0.8-1.2g:2.2-2.6g. The post-treatment includes: after the reaction is complete, the reaction system is heated to 150-160℃, and low-boiling substances are removed by vacuum distillation to obtain reversible bridged polyurethane salt.

[0019] Furthermore, the preparation method of CO2 reversible interface migration microgel powder is as follows: carboxymethyl chitosan, deionized water, and anhydrous ethanol are mixed and stirred until the system is dissolved. 8-10 wt% sodium carbonate aqueous solution is added to the reaction system to adjust the pH of the system to 8-9. Dodecyl glycidyl ether is added to the reaction system. The reaction system is heated to 45-55℃ and kept at this temperature for 4-5 hours. Genipin is added to the reaction system, and the reaction is stirred for another 3-5 hours. After post-treatment, CO2 reversible interface migration microgel powder is obtained.

[0020] The synthesis reaction mechanism of CO2 reversible interfacial migration microgel powder is as follows:

[0021] During the reaction, carboxymethyl chitosan molecules contain hydroxyl, amino, and carboxymethyl groups. Under weakly alkaline conditions, some amino and hydroxyl groups exhibit strong nucleophilic reactivity and undergo ring-opening reactions with the epoxy groups in dodecyl glycidyl ether molecules. This causes the hydrophobic dodecyl segments to graft onto the carboxymethyl chitosan molecular chain, transforming the originally hydrophilic chitosan derivative into an amphiphilic macromolecule with a hydrophilic backbone and hydrophobic side chains. This macromolecule can migrate to the oil-water interface during degreasing and insert into the oil layer through the dodecyl segments, weakening the adhesion between the oil and the aluminum profile surface. After adding genipin, genipin can undergo cross-linking reactions with the amino groups on the carboxymethyl chitosan molecular chain, forming a three-dimensional microgel network of the modified amphiphilic macromolecule. This network retains both hydrophilic groups such as carboxyl and hydroxyl groups and contains hydrophobic dodecyl segments, thus enabling stable dispersion in weakly alkaline degreasing solutions while simultaneously adsorbing, encapsulating, and agitating the oil interface. High-speed dispersion causes the cross-linked system to be sheared into micron- or submicron-sized gel particles, which are then freeze-dried to obtain microgel powder that is easy to redisperse.

[0022] In a weakly alkaline environment, the carboxyl groups of this microgel mainly exist in the form of carboxylates. The particles have strong hydration and electrostatic repulsion, which is beneficial for dispersion in degreasing solution and participation in oil removal. When CO2 is subsequently introduced to lower the pH, the carboxylates are partially protonated, the particle charge is reduced, and the hydrophobic association is enhanced. This can promote the aggregation and floating of emulsified or dispersed oil, improve the oil removal rate of the outer surface, C-shaped tank and corner code tank, and reduce the water contact angle by reducing the residual oil film. At the same time, it still maintains good tank solution regeneration capacity after 100 hours of continuous operation.

[0023] Furthermore, the ratio of carboxymethyl chitosan, deionized water, anhydrous ethanol, and dodecyl glycidyl ether is 8-10g:850mL:150mL:1.0-1.2g:0.16-0.18g. The post-processing operation includes: placing the reaction solution in a high-speed disperser, setting the rotation speed to 8000-9000r / min, dispersing at high speed for 8-10min, and then transferring the reaction solution to a freeze dryer at -30℃ for freeze drying to obtain CO2 reversible interfacial migration microgel powder.

[0024] Furthermore, in step S2, during the prewetting process in the prewetting zone, the prewetting temperature is 35-42℃ and the prewetting time is 10-30s;

[0025] During the degreasing process in the main degreasing zone, air micro-nano bubbles with a D50 particle size of 1-20μm are introduced into the phosphorus-free weak alkaline degreasing liquid through a micro-nano bubble generator. The gas-liquid volume ratio is 2-8%. The pre-wetted photovoltaic aluminum profile frame is sprayed and degreased using a pulse spraying method to obtain the degreased photovoltaic aluminum profile frame and degreasing liquid.

[0026] During the drainage process in the tank cavity drainage area, alternating air knives and low-pressure liquid knives are set in the tank cavity drainage area to drain the degreasing liquid remaining in the C-shaped groove, corner code groove, mounting hole and drainage hole, thus obtaining the drainage photovoltaic aluminum profile frame.

[0027] During the washing and drying process in the rinsing and drying zone, the drained photovoltaic aluminum profile frame enters the rinsing and drying zone. The drained photovoltaic aluminum profile frame undergoes a first-stage countercurrent rinsing and a second-stage countercurrent rinsing in sequence, and then is dried with hot air at 80-90℃ for 5-7 minutes to obtain the degreased photovoltaic aluminum profile frame.

[0028] Furthermore, during the degreasing process, the spray pressure of the spray degreasing is 0.15-0.35MPa, the pulse cycle is 3-6s spray and 1-3s stop spray, and the pre-wetted photovoltaic aluminum profile frame is intermittently oscillating at an angle of 8-20° during the degreasing process, and the degreasing time is 120-180s.

[0029] The air knife pressure is 0.15-0.20 MPa, and the low-pressure liquid knife pressure is 0.08-0.1 MPa. The air knife and the low-pressure liquid knife are used alternately 3-5 times.

[0030] The temperature of the first-stage countercurrent rinse is 25-40℃, and the rinsing time is 20-40s; the temperature of the second-stage countercurrent rinse is 20-35℃, and the rinsing time is 20-40s. The conductivity of the second-stage rinse water is less than 200μS / cm.

[0031] Furthermore, the preparation method of the degreasing regeneration solution is as follows: the degreasing solution collected in the main degreasing zone and the tank cavity drainage zone is transported to the regeneration tank, CO2 is introduced into the regeneration tank to lower the pH of the degreasing solution to 6.8-7.6, and the solution is kept in the regeneration tank for 3-6 minutes. Then, the degreasing solution is transported to the oil-water separator and kept for 5-7 minutes. The released composite oil sludge aggregates and floats to the surface and is discharged. The lower layer of liquid is filtered using a filter membrane with a pore size of 0.1-1.0 μm. Air is introduced into the liquid, and sodium hydroxide is added at the same time to adjust the pH of the degreasing solution to 9.2-9.8 to obtain the degreasing regeneration solution. The degreasing regeneration solution is then returned to the main degreasing zone for recycling.

[0032] The present invention has the following beneficial effects:

[0033] 1. This invention utilizes a weak alkaline buffer system formed by sodium carbonate and sodium bicarbonate to promote the neutralization of acidic oil stains and the saponification of some ester-based oil stains, while avoiding significant corrosion of the aluminum substrate and its oxide film by strong alkali. Alkyl glycosides and low-foaming surfactants enhance wetting and emulsifying capabilities, while tetrasodium glutamate diacetate and sodium gluconate inhibit metal ion-induced soap scum and deposition. CO2 reversible interfacial migration microgel powder inserts into the oil stain interface through hydrophobic segments, and reversibly bridging polyurethane salts achieve oil stain capture, dispersion, and complexation through carboxylates, hydrophobic segments, and amine groups, thereby reducing the interfacial bonding force between oil stains and the aluminum surface, allowing the organic oil film to be fully peeled off. This improves the oil removal rate, reduces the water contact angle, and simultaneously provides phosphorus-free environmental protection and aluminum surface protection.

[0034] 2. This invention also utilizes a low-surface-tension degreasing liquid to pre-wet the tank cavity and pores, eliminating localized air retention and allowing the oil contaminants in the inner cavity to be pre-wetted, swollen, and loosened. During the main degreasing stage, air micro- and nano-bubbles with a particle size of 1-20 μm can enter narrow areas that are difficult to fully renew with conventional liquid flow, and promote oil desorption through bubble adsorption, interface disturbance, and local micro-mixing. Pulse spraying provides impact shear force during the spraying stage and promotes rewetting of the degreasing liquid and migration of contaminants during the spray-off stage. Intermittent oscillation of the profile tilt angle further changes the fluid direction in the tank cavity, reducing cleaning dead zones. Thus, the chemical interface stripping effect and the physical enhanced mass transfer effect work together to maintain a high oil removal rate on the outer surface, C-shaped groove, and corner code groove, while keeping the water contact angle in the inner cavity at a low level.

[0035] 3. This invention also uses alternating air knives and low-pressure liquid knives to discharge oily residues from C-shaped grooves, corner grooves, and pores, preventing emulsified oil and surfactant residues from back-adheding during subsequent rinsing and drying. Primary and secondary countercurrent rinsing and low conductivity control further reduce salt, complexing agent, and oil residues, while hot air drying reduces watermarks and secondary adsorption pollution. During continuous operation, CO2 is introduced into the regeneration tank to lower the pH of the system, causing protonation of carboxylates and tertiary amines in microgels and polyaspartate, as well as changes in hydrophilicity and hydrophobicity balance. This promotes charge neutralization, hydrophobic association, and bridging aggregation of emulsified oil droplets, leading to their floating and separation. Subsequently, filtration and air aeration restore the weak alkalinity, allowing the functional components to redisperse and return to a degreasing state. This enables the degreasing liquid to both disperse and remove oil during use and aggregate and remove oil during regeneration, thereby reducing cleaning degradation caused by oil accumulation and ensuring a stable oil removal rate and low water contact angle even after 100 hours of continuous operation. Detailed Implementation

[0036] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0037] In this application, the degree of substitution of carboxymethyl chitosan is 85%;

[0038] In this application, polysuccinimide is a commercially available product with an active ingredient content of 99% and a molecular weight of 5000-15000.

[0039] In this application, the alkyl glycoside is commercially available alkyl glycoside APG0810, with an active ingredient content of 99%;

[0040] In this application, the low-foaming surfactant is commercially available lauryl alcohol polyoxypropylene polyoxyethylene ether, with an effective ingredient content of 99%;

[0041] In this application, the defoamer is a commercially available polyether defoamer, model SGR1800.

[0042] Example 1

[0043] This embodiment provides a method for preparing a phosphorus-free, weakly alkaline degreasing solution, including the following steps:

[0044] Step 1: Preparation of CO2 reversible interfacial migration microgel powder

[0045] Weigh out 80g of carboxymethyl chitosan, 8500mL of deionized water, and 1500mL of anhydrous ethanol and add them to a reaction flask. Stir until the system is dissolved. Add 8wt% sodium carbonate aqueous solution to the reaction flask to adjust the pH of the system to 8. Add 10g of dodecyl glycidyl ether to the reaction flask. Heat the reaction flask to 45℃ and keep it at that temperature for 4 hours. Add 1.6g of genipin to the reaction system and continue stirring for 3 hours. Place the reaction solution in a high-speed disperser and set the speed to 8000r / min. Disperse at high speed for 8 minutes. Then transfer the reaction solution to a freeze dryer at -30℃ and freeze dry to obtain CO2 reversible interfacial migration microgel powder.

[0046] Step 2: Preparation of reversible bridged polyurethane salt

[0047] Weigh 100g of polysuccinimide and 600mL of N-methylpyrrolidone and add them to a reaction flask. Stir the mixture and heat it to 55℃. Stir until the system is dissolved. Add laurylamine and 8g of N,N-dimethyl-1,3-propanediamine to the reaction flask and keep it at this temperature for 6 hours. Add 3mol / L sodium hydroxide aqueous solution to the reaction system to adjust the pH to 9 and keep it at this temperature for 3 hours. Heat the reaction flask to 150℃ and remove low-boiling substances by vacuum distillation to obtain reversible bridged polyurethane salt.

[0048] Step 3: Prepare phosphorus-free, weakly alkaline degreasing solution

[0049] Sodium carbonate and sodium bicarbonate are mixed in a weight ratio of 3:2 to obtain a mixed alkali;

[0050] Weigh 10L of deionized water and add it to the reaction vessel. Stir the mixture and add it to the reaction vessel to adjust the pH of the system to 9. Add 2.6g of alkyl glycoside, 1.1g of low-foaming surfactant, 9g of tetrasodium diacetate of glutamic acid, 4g of sodium gluconate, 2.2g of reversible bridging polyurethane salt, 4g of CO2 reversible interfacial migration microgel powder, 0.3g of tannic acid, and 0.3g of defoamer to the reaction flask. Heat the reaction flask to 50℃ and stir until the system dissolves. Adjust the pH of the system to 9.2 to obtain a phosphorus-free weakly alkaline degreasing solution.

[0051] Example 2

[0052] This embodiment provides a method for preparing a phosphorus-free, weakly alkaline degreasing solution, including the following steps:

[0053] Step 1: Preparation of CO2 reversible interfacial migration microgel powder

[0054] Weigh out 90g of carboxymethyl chitosan, 8500mL of deionized water, and 1500mL of anhydrous ethanol and add them to a reaction flask. Stir until the system is dissolved. Add 9wt% sodium carbonate aqueous solution to the reaction flask to adjust the pH of the system to 8.5. Add 11g of dodecyl glycidyl ether to the reaction flask. Heat the reaction flask to 50℃ and keep it at that temperature for 4.5h. Add 1.7g of genipin to the reaction system and continue stirring for 4h. Place the reaction solution in a high-speed disperser and set the speed to 8500r / min for high-speed dispersion for 9min. Then transfer the reaction solution to a freeze dryer at -30℃ and freeze dry to obtain CO2 reversible interfacial migration microgel powder.

[0055] Step 2: Preparation of reversible bridged polyurethane salt

[0056] Weigh 100g of polysuccinimide and 800mL of N-methylpyrrolidone and add them to a reaction flask. Stir the mixture and heat it to 60℃. Stir until the system is dissolved. Add laurylamine and 10g of N,N-dimethyl-1,3-propanediamine to the reaction flask and keep it at this temperature for 7h. Add 4mol / L sodium hydroxide aqueous solution to the reaction system to adjust the pH to 9.5 and keep it at this temperature for 3.5h. Heat the reaction flask to 155℃ and remove low-boiling substances by vacuum distillation to obtain reversible bridged polyurethane salt.

[0057] Step 3: Prepare phosphorus-free, weakly alkaline degreasing solution

[0058] Sodium carbonate and sodium bicarbonate are mixed in a weight ratio of 3:2 to obtain a mixed alkali;

[0059] Weigh 10L of deionized water and add it to the reaction vessel. Stir the mixture and add a mixed alkali to the reaction vessel to adjust the pH of the system to 9.5. Add 3.0g of alkyl glycoside, 1.3g of low-foaming surfactant, 10.5g of tetrasodium diacetate of glutamic acid, 5g of sodium gluconate, 2.4g of reversible bridged polyurethane salt, 4.5g of CO2 reversible interfacial migration microgel powder, 0.4g of tannic acid, and 0.4g of defoamer to the reaction flask. Heat the reaction flask to 55℃ and stir until the system dissolves. Adjust the pH of the system to 9.5 to obtain a phosphorus-free weakly alkaline degreasing solution.

[0060] Example 3

[0061] This embodiment provides a method for preparing a phosphorus-free, weakly alkaline degreasing solution, including the following steps:

[0062] Step 1: Preparation of CO2 reversible interfacial migration microgel powder

[0063] Weigh out 100g of carboxymethyl chitosan, 8500mL of deionized water, and 1500mL of anhydrous ethanol and add them to a reaction flask. Stir until the system is dissolved. Add 10wt% sodium carbonate aqueous solution to the reaction flask to adjust the pH of the system to 9. Add 12g of dodecyl glycidyl ether to the reaction flask. Heat the reaction flask to 55℃ and keep it at that temperature for 5h. Add 1.8g of genipin to the reaction system and continue stirring for 5h. Place the reaction solution in a high-speed disperser and set the speed to 9000r / min. Disperse at high speed for 10min. Then transfer the reaction solution to a freeze dryer at -30℃ and freeze dry to obtain CO2 reversible interfacial migration microgel powder.

[0064] Step 2: Preparation of reversible bridged polyurethane salt

[0065] Weigh 100g of polysuccinimide and 1000mL of N-methylpyrrolidone and add them to a reaction flask. Stir the mixture and heat it to 65℃. Stir until the system dissolves. Add laurylamine and 12g of N,N-dimethyl-1,3-propanediamine to the reaction flask and keep it at this temperature for 8 hours. Add 5mol / L sodium hydroxide aqueous solution to the reaction system to adjust the pH to 10 and keep it at this temperature for 4 hours. Heat the reaction flask to 160℃ and remove low-boiling substances by vacuum distillation to obtain reversible bridged polyurethane salt.

[0066] Step 3: Prepare phosphorus-free, weakly alkaline degreasing solution

[0067] Sodium carbonate and sodium bicarbonate are mixed in a weight ratio of 3:2 to obtain a mixed alkali;

[0068] Weigh out 10L of deionized water and add it to the reaction vessel. Stir the mixture and add it to the reaction vessel to adjust the pH of the system to 10. Add 3.5g of alkyl glycoside, 1.5g of low-foaming surfactant, 12g of tetrasodium diacetate of glutamic acid, 6g of sodium gluconate, 2.6g of reversible bridged polyurethane salt, 5g of CO2 reversible interfacial migration microgel powder, 0.5g of tannic acid, and 0.5g of defoamer to the reaction flask. Heat the reaction flask to 60℃ and stir until the system dissolves. Adjust the pH of the system to 9.8 to obtain a phosphorus-free weakly alkaline degreasing solution.

[0069] Example 4

[0070] This embodiment provides an environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames, including the following steps:

[0071] Step S1, Prewetting

[0072] The phosphorus-free weak alkaline degreasing solution prepared in Example 1 was added to the degreasing tank, and the temperature of the degreasing solution was controlled at 35°C and the pH at 9.2.

[0073] The photovoltaic aluminum profile frame to be processed is placed on the conveyor hanger. The photovoltaic aluminum profile frame enters the pre-wetting area and is immersed in the phosphorus-free weak alkaline degreasing liquid for 10 seconds. The phosphorus-free weak alkaline degreasing liquid enters the C-shaped groove, corner code groove, mounting hole and drainage hole to obtain the pre-wetted photovoltaic aluminum profile frame.

[0074] Step S2, Degreasing

[0075] The pre-wetted photovoltaic aluminum profile frame enters the main degreasing zone. Air micro-nano bubbles with a D50 particle size of 1-20μm are introduced into the phosphorus-free weak alkaline degreasing solution through a micro-nano bubble generator. The gas-liquid volume ratio is 2%. The pre-wetted photovoltaic aluminum profile frame is degreased by pulse spraying. The spraying pressure is set to 0.15MPa, and the pulse cycle is 3 sprays followed by 1 second of stop spraying. During the degreasing process, the pre-wetted photovoltaic aluminum profile frame is intermittently oscillating at an 8° tilt angle. The degreasing time is 120s, resulting in a degreased photovoltaic aluminum profile frame and degreasing solution.

[0076] Step S3, Drainage

[0077] The degreased photovoltaic aluminum profile frame enters the draining area of ​​the tank cavity. The draining area of ​​the tank cavity is equipped with alternating air knives and low-pressure liquid knives. The air knife pressure is set to 0.15MPa and the low-pressure liquid knife pressure is set to 0.08MPa. The air knife and low-pressure liquid knife work alternately 3 times to drain the degreased liquid remaining in the C-shaped groove, corner code groove, mounting hole and drain hole, thus obtaining the drained photovoltaic aluminum profile frame.

[0078] Step S4: Washing and drying

[0079] The drained photovoltaic aluminum profile frame enters the rinsing and drying zone, where it undergoes a first-stage countercurrent rinsing and a second-stage countercurrent rinsing. The first-stage countercurrent rinsing water temperature is set at 25℃ and the rinsing time is 20s; the second-stage countercurrent rinsing water temperature is set at 20℃ and the rinsing time is 20s. Then, it is dried with hot air at 80℃ for 5 minutes to obtain the degreased photovoltaic aluminum profile frame. The conductivity of the second-stage rinsing water is less than 200μS / cm.

[0080] Step S5: Degreasing solution regeneration

[0081] In the continuous degreasing process, the degreasing liquid collected in the main degreasing zone and the tank drainage zone is transported to the regeneration tank. Then, CO2 is introduced into the regeneration tank to lower the pH of the degreasing liquid to 6.8. The liquid is then left to stand in the regeneration tank for 3 minutes. After that, the degreasing liquid is transported to the oil-water separator and left to stand for 5 minutes. The released complex oil sludge aggregates and floats to the surface before being discharged. The lower layer of liquid is filtered through a filter membrane with a pore size of 0.1-1.0 μm. Air is then introduced into the lower layer and aerated until the pH of the degreasing liquid rises back to 9.2, yielding the degreasing regeneration liquid. This regeneration liquid is then returned to the main degreasing zone for continued use.

[0082] Example 5

[0083] This embodiment provides an environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames, including the following steps:

[0084] Step S1, Prewetting

[0085] The phosphorus-free weakly alkaline degreasing solution prepared in Example 2 was added to the degreasing tank, and the temperature of the degreasing solution was controlled at 39°C and the pH at 9.5.

[0086] The photovoltaic aluminum profile frame to be processed is placed on the conveyor hanger. The photovoltaic aluminum profile frame enters the pre-wetting area and is immersed in a phosphorus-free weak alkaline degreasing solution for 20 seconds. The phosphorus-free weak alkaline degreasing solution enters the C-shaped groove, corner code groove, mounting hole and drainage hole to obtain the pre-wetted photovoltaic aluminum profile frame.

[0087] Step S2, Degreasing

[0088] The pre-wetted photovoltaic aluminum profile frame enters the main degreasing zone. Air micro-nano bubbles with a D50 particle size of 1-20μm are introduced into the phosphorus-free weak alkaline degreasing solution through a micro-nano bubble generator. The gas-liquid volume ratio is 5%. The pre-wetted photovoltaic aluminum profile frame is degreased by pulse spraying. The spraying pressure is set to 0.25MPa, and the pulse cycle is 4s spraying and 2s stopping. During the degreasing process, the pre-wetted photovoltaic aluminum profile frame is intermittently oscillating at a 14° tilt angle. The degreasing time is 150s, resulting in a degreased photovoltaic aluminum profile frame and degreasing solution.

[0089] Step S3, Drainage

[0090] The degreased photovoltaic aluminum profile frame enters the drainage area of ​​the tank cavity. The drainage area of ​​the tank cavity is equipped with alternating air knives and low-pressure liquid knives. The air knife pressure is set to 0.17MPa and the low-pressure liquid knife pressure is set to 0.09MPa. The air knife and low-pressure liquid knife work alternately 4 times to drain the degreased liquid remaining in the C-shaped groove, corner code groove, mounting hole and drainage hole, thus obtaining the drained photovoltaic aluminum profile frame.

[0091] Step S4: Washing and drying

[0092] The drained photovoltaic aluminum profile frame enters the rinsing and drying zone, where it undergoes a first-stage countercurrent rinsing and a second-stage countercurrent rinsing. The first-stage countercurrent rinsing water temperature is set at 32℃, and the rinsing time is 30s; the second-stage countercurrent rinsing water temperature is set at 28℃, and the rinsing time is 30s. Then, it is dried with hot air at 85℃ for 6 minutes to obtain the degreased photovoltaic aluminum profile frame. The conductivity of the second-stage rinsing water is less than 200μS / cm.

[0093] Step S5: Degreasing solution regeneration

[0094] In the continuous degreasing process, the degreasing liquid collected in the main degreasing zone and the tank drainage zone is transported to the regeneration tank. Then, CO2 is introduced into the regeneration tank to lower the pH of the degreasing liquid to 7.2. The liquid is then held in the regeneration tank for 4.5 minutes. After that, the degreasing liquid is transported to the oil-water separator and held for 6 minutes. The released complex oil sludge aggregates and floats to the surface before being discharged. The lower layer of liquid is filtered through a filter membrane with a pore size of 0.1-1.0 μm. Air is introduced into the lower layer and aerated until the pH of the degreasing liquid rises back to 9.5, resulting in degreasing regeneration liquid. This regeneration liquid is then returned to the main degreasing zone for continued use.

[0095] Example 6

[0096] This embodiment provides an environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames, including the following steps:

[0097] Step S1, Prewetting

[0098] The phosphorus-free weakly alkaline degreasing solution prepared in Example 3 was added to the degreasing tank, and the temperature of the degreasing solution was controlled at 42°C and the pH at 9.8.

[0099] The photovoltaic aluminum profile frame to be processed is placed on the conveyor hanger. The photovoltaic aluminum profile frame enters the pre-wetting area and is immersed in a phosphorus-free weak alkaline degreasing solution for 30 seconds. The phosphorus-free weak alkaline degreasing solution enters the C-shaped groove, corner code groove, mounting hole and drainage hole to obtain the pre-wetted photovoltaic aluminum profile frame.

[0100] Step S2, Degreasing

[0101] The pre-wetted photovoltaic aluminum profile frame enters the main degreasing zone. Air micro-nano bubbles with a D50 particle size of 1-20μm are introduced into the phosphorus-free weak alkaline degreasing solution through a micro-nano bubble generator. The gas-liquid volume ratio is 8%. The pre-wetted photovoltaic aluminum profile frame is degreased by pulse spraying. The spraying pressure is set to 0.35MPa, and the pulse cycle is 6s spraying and 3s stopping. During the degreasing process, the pre-wetted photovoltaic aluminum profile frame is intermittently oscillating at a 20° tilt angle. The degreasing time is 180s, resulting in a degreased photovoltaic aluminum profile frame and degreasing solution.

[0102] Step S3, Drainage

[0103] The degreased photovoltaic aluminum profile frame enters the draining area of ​​the tank cavity. The draining area of ​​the tank cavity is equipped with alternating air knives and low-pressure liquid knives. The air knife pressure is set to 0.20MPa and the low-pressure liquid knife pressure is set to 0.1MPa. The air knife and low-pressure liquid knife alternately act 5 times to drain the degreased liquid remaining in the C-shaped groove, corner code groove, mounting hole and drain hole, thus obtaining the drained photovoltaic aluminum profile frame.

[0104] Step S4: Washing and drying

[0105] The drained photovoltaic aluminum profile frame enters the rinsing and drying zone, where it undergoes a first-stage countercurrent rinsing and a second-stage countercurrent rinsing. The first-stage countercurrent rinsing water temperature is set at 40℃ and the rinsing time is 40s; the second-stage countercurrent rinsing water temperature is set at 35℃ and the rinsing time is 40s. Then, it is dried with hot air at 90℃ for 7 minutes to obtain the degreased photovoltaic aluminum profile frame. The conductivity of the second-stage rinsing water is less than 200μS / cm.

[0106] Step S5: Degreasing solution regeneration

[0107] In the continuous degreasing process, the degreasing liquid collected in the main degreasing zone and the tank cavity drainage zone is transported to the regeneration tank. Then, CO2 is introduced into the regeneration tank to lower the pH of the degreasing liquid to 7.6. The liquid is then left to stand in the regeneration tank for 6 minutes. After that, the degreasing liquid is transported to the oil-water separator and left to stand for 7 minutes. The released complex oil sludge aggregates and floats to the surface and is then discharged. The lower layer of liquid is filtered through a filter membrane with a pore size of 0.1-1.0 μm. Air is then introduced into the lower layer and aerated until the pH of the degreasing liquid rises back to 9.8, resulting in degreasing regeneration liquid. This regeneration liquid is then returned to the main degreasing zone for continued use.

[0108] Comparative Example 1

[0109] The difference between this comparative example and Example 6 is that the phosphorus-free weak alkaline degreasing solution used was not prepared with CO2 reversible interfacial migration microgel powder.

[0110] Comparative Example 2

[0111] The difference between this comparative example and Example 6 is that the phosphorus-free weak alkaline degreasing solution used was not prepared with reversibly bridged polyurethane salt.

[0112] Comparative Example 3

[0113] The difference between this comparative example and Example 6 is that, in step S2, no air microbubbles were introduced into the phosphorus-free weak alkaline degreasing solution.

[0114] Performance testing:

[0115] The environmentally friendly and efficient photovoltaic aluminum profile frame degreasing process described in Examples 4-6 and Comparative Examples 1-3 was continuously run for 100 hours, and the degreased photovoltaic aluminum profile frame after 100 hours of continuous operation was taken as the test sample.

[0116] The amount of grease residue on the outer surface, C-groove, and corner code groove of the test sample was determined according to standard JB / T 6896-2007 "Surface Cleanliness of Air Separation Equipment", and the formula was used as a reference. The grease removal rate of the sample is determined, where P0 is the amount of grease residue in the sample before degreasing and cleaning, and P1 is the amount of grease residue in the sample.

[0117] The water contact angles of the outer surface, bottom of the C-groove, and corner code groove of the test sample were determined according to the standard GB / T 30693-2014 "Measurement of Water Contact Angle of Plastic Film". The specific test data are shown in Table 1 below.

[0118] Table 1 - Performance Test Data of the Sample to be Tested

[0119]

[0120] Data Analysis:

[0121] Comparative analysis of the data in Table 1 shows that the grease removal rate on the outer surface of the test sample of this invention reaches 96.7-97.1%, and the water contact angle reaches 23.0-23.6°; the grease removal rate at the C-groove reaches 95.8-96.2%, and the water contact angle reaches 25.1-25.7°; the grease removal rate at the corner groove reaches 94.5-95.0%, and the water contact angle reaches 26.2-26.6°. All performance test values ​​are superior to the comparative example, indicating that this invention, through phosphorus-free weakly alkaline degreasing liquid, CO2-responsive functional components, and micro / nano bubbles... The system combines pulse spraying and CO2 regeneration cycle to remove oil stains and reduce corrosion of aluminum materials using a weak alkaline buffer system. CO2 reversible interface migration microgel powder and reversible bridging polyurethane salt can enhance the oil stain removal, dispersion and regeneration separation effect. Micro-nano bubbles and supporting cleaning processes can improve the cleaning uniformity of complex structural parts such as C-shaped grooves and corner code grooves, achieving efficient and environmentally friendly degreasing of photovoltaic aluminum profile frames. It maintains the oil removal rate and water contact angle after 100 hours of continuous operation, thus maintaining a good degreasing effect and combining phosphorus-free environmental protection with continuous operation stability.

[0122] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. An environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames, characterized in that, Includes the following steps: S1. Add sodium carbonate and sodium bicarbonate to deionized water, adjust the pH of the system to 9-10, add alkyl glycoside, low foaming surfactant, tetrasodium glutamate diacetate, sodium gluconate, reversible bridging polyurethane salt, CO2 reversible interfacial migration microgel powder, tannic acid, and defoamer to the reaction system, heat the reaction system to 50-60℃, and stir until the system is dissolved to obtain a phosphorus-free weak alkaline degreasing solution. S2. Add phosphorus-free weak alkaline degreasing solution to the degreasing tank, control the temperature of the degreasing solution to 35-42℃ and the pH to 9.2-9.8, place the photovoltaic aluminum profile frame to be treated on the conveyor hanger, and let the photovoltaic aluminum profile frame pass through the pre-wetting zone for pre-wetting, the main degreasing zone for degreasing, the tank cavity drainage zone for drainage, and the rinsing and drying zone for washing and drying to obtain the degreased photovoltaic aluminum profile frame. S3. During the degreasing process, the degreasing liquid collected in the main degreasing zone and the draining zone of the tank cavity is transported to the regeneration tank for regeneration to obtain degreasing regeneration liquid, which is then recycled for reuse.

2. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 1, characterized in that, In step S1, the weight ratio of sodium carbonate to sodium bicarbonate is 3:2, and the dosage ratio of deionized water, alkyl glycoside, low-foaming surfactant, tetrasodium diacetate of glutamate, sodium gluconate, reversible bridging polyurethane salt, CO2 reversible interfacial migration microgel powder, tannic acid, and defoamer is 1L:0.26-0.35g:0.11-0.15g:0.9-1.2g:0.4-0.6g:0.22-0.26g:0.4-0.5g:0.03-0.05g:0.03-0.05g.

3. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 1, characterized in that, The preparation method of reversible bridged polyurethane salt is as follows: polysuccinimide and N-methylpyrrolidone are mixed and stirred, the reaction system is heated to 55-65℃ and stirred until the system is dissolved. Laurylamine and N,N-dimethyl-1,3-propanediamine are added to the reaction system and the reaction is kept at the temperature for 6-8 hours. Sodium hydroxide aqueous solution is added to the reaction system to adjust the pH of the system to 9-10 and the reaction is kept at the temperature for 3-4 hours. After post-treatment, reversible bridged polyurethane salt is obtained.

4. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 3, characterized in that, The ratio of polysuccinimide, N-methylpyrrolidone, laurylamine, and N,N-dimethyl-1,3-propanediamine is 10g:60-100mL:0.8-1.2g:2.2-2.6g.

5. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 1, characterized in that, The preparation method of CO2 reversible interfacial migration microgel powder is as follows: carboxymethyl chitosan, deionized water, and anhydrous ethanol are mixed and stirred until the system is dissolved. 8-10 wt% sodium carbonate aqueous solution is added to the reaction system to adjust the pH of the system to 8-9. Dodecyl glycidyl ether is added to the reaction system. The reaction system is heated to 45-55℃ and kept at this temperature for 4-5 hours. Genipin is added to the reaction system, and the reaction is stirred for another 3-5 hours. After post-treatment, CO2 reversible interfacial migration microgel powder is obtained.

6. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 5, characterized in that, The ratio of carboxymethyl chitosan, deionized water, anhydrous ethanol and dodecyl glycidyl ether is 8-10g:850mL:150mL:1.0-1.2g:0.16-0.18g.

7. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 1, characterized in that, In step S2, during the prewetting process in the prewetting zone, the prewetting temperature is 35-42℃ and the prewetting time is 10-30s; During the degreasing process in the main degreasing zone, air micro-nano bubbles with a D50 particle size of 1-20μm are introduced into the phosphorus-free weak alkaline degreasing liquid through a micro-nano bubble generator. The gas-liquid volume ratio is 2-8%. The pre-wetted photovoltaic aluminum profile frame is sprayed and degreased using a pulse spraying method to obtain the degreased photovoltaic aluminum profile frame and degreasing liquid. During the drainage process in the tank cavity drainage area, alternating air knives and low-pressure liquid knives are set in the tank cavity drainage area to drain the degreasing liquid remaining in the C-shaped groove, corner code groove, mounting hole and drainage hole, thus obtaining the drainage photovoltaic aluminum profile frame. During the washing and drying process in the rinsing and drying zone, the drained photovoltaic aluminum profile frame enters the rinsing and drying zone. The drained photovoltaic aluminum profile frame undergoes a first-stage countercurrent rinsing and a second-stage countercurrent rinsing in sequence, and then is dried with hot air at 80-90℃ for 5-7 minutes to obtain the degreased photovoltaic aluminum profile frame.

8. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 7, characterized in that, During the degreasing process, the spray pressure of the spray degreasing is 0.15-0.35MPa, the pulse cycle is 3-6s spray and 1-3s stop spray. During the degreasing process, the pre-wetted photovoltaic aluminum profile frame is intermittently oscillated at an angle of 8-20°, and the degreasing time is 120-180s. The air knife pressure is 0.15-0.20 MPa, and the low-pressure liquid knife pressure is 0.08-0.1 MPa. The air knife and the low-pressure liquid knife are used alternately 3-5 times. The temperature of the first-stage countercurrent rinse is 25-40℃, and the rinsing time is 20-40s; the temperature of the second-stage countercurrent rinse is 20-35℃, and the rinsing time is 20-40s. The conductivity of the second-stage rinse water is less than 200μS / cm.

9. The environmentally friendly and efficient degreasing process for photovoltaic aluminum profile frames according to claim 7, characterized in that, The preparation method of degreasing regeneration solution is as follows: the degreasing solution collected in the main degreasing zone and the tank cavity drainage zone is transported to the regeneration tank. CO2 is introduced into the regeneration tank to lower the pH of the degreasing solution to 6.8-7.

6. The solution is then left in the regeneration tank for 3-6 minutes. The degreasing solution is then transported to an oil-water separator and left for 5-7 minutes. The released composite oil sludge aggregates and floats to the surface and is then discharged. The lower layer of liquid is filtered using a filter membrane with a pore size of 0.1-1.0 μm. Air is introduced into the liquid, and sodium hydroxide is added during aeration to adjust the pH of the degreasing solution to 9.2-9.8, thus obtaining the degreasing regeneration solution. The degreasing regeneration solution is then returned to the main degreasing zone for recycling.